2022
DOI: 10.1038/s41477-022-01112-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial control of potato tuberization by the TCP transcription factor BRANCHED1b

Abstract: The control of carbon allocation, storage and usage is critical for plant growth and development and is exploited for both crop food production and CO 2 capture. Potato tubers are natural carbon reserves in the form of starch that have evolved to allow propagation and survival over winter. They form from stolons, below ground, where they are protected from cold temperatures and animal foraging. We show that BRANCHED1b (BRC1b) acts as a tuberisation repressor in aerial axillary buds, which prevents buds from co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…However, the molecular mechanism of flowering and branching remains elusive. Some proteins interacting with StSP6A have been reported, including StFDL1, StABL1, StSWEET11, and BRC1b [ 6 , 7 , 8 , 9 , 11 ]. It is important to explore whether there are some other unknown StSP6A interactors involved in other functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the molecular mechanism of flowering and branching remains elusive. Some proteins interacting with StSP6A have been reported, including StFDL1, StABL1, StSWEET11, and BRC1b [ 6 , 7 , 8 , 9 , 11 ]. It is important to explore whether there are some other unknown StSP6A interactors involved in other functions.…”
Section: Discussionmentioning
confidence: 99%
“…In potato, StSP6A interacts with the SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTER 11 (StSWEET11) to promote the symplastic transport of sucrose to affect the source-sink pathway of tuberization [ 8 ]. It has been also reported that StSP6A is involved in branching and flowering [ 9 , 10 ]. A TCP transcription factor, BRANCHED1b (BRC1b), interacts with StSP6A to promote dormancy and repress tuberization [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root depth (deep or shallow) is an important agronomic trait related to yield potential and is particularly important in potato tubers ( Xu et al., 2017 ; Wang et al., 2020b ). In potato tubers, root development begins at tuber germination, and the first young buds appear with scaly or “embryo” leaves at the top, followed by young roots on several sections at the base of the buds ( Nicolas et al., 2022 ). The early period is primarily for root formation and bud growth, which form the basis for tuber seedling rooting, tuber formation, and plant strengthening ( Zhou et al., 2017 ; Omary et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…After our manuscript was accepted in principle, a study by Nicolas et al 1 showed that BRANCHED1b acts as a tuberization repressor in aerial axillary buds in tetraploid potato. We note that IT1 and BRANCHED1b are the same gene.…”
mentioning
confidence: 99%